Advances in bismuth-based topological quantum materials by scanning tunneling microscopy. (1st September 2022) - Li, Yaqi; Zhang, Jingwei; Xu, Xun; Hao, Weichang; Zhuang, Jincheng; Du, Yi
Abstract: In recent years, topological quantum materials (TQMs) have attracted intensive attention in the area of condensed matter physics due to their novel topologies and their promising applications in quantum computing, spin electronics and next-generation integrated circuits. Scanning tunneling microscopy/spectroscopy (STM/STS) is regarded as a powerful technique to characterize the local density of states with atomic resolution, which is ideally suited to the measurement of the bulk-boundary correspondence of TQMs. In this review, using STM/STS, we focus on recent research on bismuth-based TQMs, including quantum-spin Hall insulators, 3D weak topological insulators (TIs), high-order TIs, topological Dirac semi-metals and dual TIs. Efficient methods for the modulation of the topological properties of the TQMs are introduced, such as interlayer interaction, thickness variation and local electric field perturbation. Finally, the challenges and prospects for this field of study are discussed.